The sleep of others and the transformations of sleep research - Kroker, Kenton (University of Toronto Press, 2007)
"We tend to think of sleep as a private concern, a night-time retreat from the physical world into the realm of the subconscious. Yet sleep also has a public side; it has been the focal point of religious ritual, philosophic speculation, political debate, psychological research, and more recently, neuroscientific investigation and medical practice." "In this history of sleep research, Kenton Kroker draws on a wide range of material to present the story of how an investigative field - at one time dominated by the study of dreams - slowly morphed into a laboratory-based discipline. The result of this transformation, Kroker argues, has changed the very meaning of sleep from its earlier conception to an issue for public health and biomedical intervention."